IMPLEMENTASI PENDIDIKAN KARAKTER DALAM MENANAMKAN SIKAP RELIGIUS DI MIN NANJUNGAN KECAMATAN PINO RAYA KABUPATEN BENGKULU SELATAN - Pirman Joyo; Nan surto (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2020)
The purpose of this research  is to know the steps  of implementation and  implementation of character education in instilling students  ‘religious attitude,  as well as supporting and  inhibiting factors to instill students’  religious attitude  in MIN Nanjungan Pino Raya District, South Bengkulu Regency.  The formulation of this research  problem  is how the character educa- tion steps in instilling students  ‘religious attitude  in MIN? how to implement  character education in instilling students’  religious attitude  in MIN? and supporting factors and barriers to instill the religious attitude  of students  in MIN Nanjungan Pino Sub Raya Bengkulu  Selatan  Regency?  This research  is a qualitative  research  with inductive  analysis. The data  collection of this research was  conducted by direct  researchers. Techniques used  for data  retrieval  are  observation, wawancara, documentation and checklist. The result of this research  is character education is already  present  in the content  in K.13 curriculum.  The findings of researchers in this study: first step implementation implemented by MIN Nanjungan on character education in instilling the reli- gious attitude  of their students  by forming religious teachers. Religious coach is a teacher  appointed by the head  of a madrasah to coordinate religious activities. The special step taken  in instilling students’  religious attitude  is to create  a control card.  The card aims to control the prayer time of five children when the child is outside Madrasah. Both implementation of character edu- cation in instilling students’ religious attitude  through  intra and extracurricular. Intra-curricular through  the learning approach in the classroom. Being extra-curricular through  programs created  by religious coaches